ASBAB AN-NUZUL - Hakmi Hidayat; Citra Aviva Umaira; Rizki Mustika Trijayanti; Muhammad Hannan Ali; Alqodhi Adlantama (CV. ITTC INDONESIA, 2024)
This research aims to reveal the existence and importance of Asbāb al-nuzūl Al-Qur'an in the context of interpreting and discovering its legal substance. This research is based on the importance of the benefits and urgency of Asbāb al-nuzūl Al- Qur'an in the digital era so that it is not forgotten by current developments and pros and cons attitudes among ulama in facing the existence of Asbāb al-nuzūl Al-Qur'an. Most scholars believe that knowledge of Asbāb al-nuzūl based on history is very important in understanding the contents of the verse, but the opinion of others is the opposite. This research is a type of library research that involves critical analysis. The data analysis method used is inductive and comparative. The results of this study show that it is important and useful to consider the existence and urgency of the Asbāb al-nuzūl verses of the Qur'an in understanding its laws